Recent progress of theoretical studies on electro- and photo-chemical conversion of CO2 with single-atom catalysts. Issue 9 (16th February 2023) - Jiang, Liyun; Yang, Qingqing; Xia, Zhaoming; Yu, Xiaohu; Zhao, Mengdie; Shi, Qiping; Yu, Qi
Abstract : Recent progress of theoretical studies on electro- and photo- chemical conversion of CO2 with single-atom catalysts has been presented, from the intermediates to the final products. Abstract : The CO2 reduction reaction (CO2 RR) into chemical products is a promising and efficient way to combat the global warming issue and greenhouse effect. The viability of the CO2 RR critically rests with finding highly active and selective catalysts that can accomplish the desired chemical transformation. Single-atom catalysts (SACs) are ideal in fulfilling this goal due to the well-defined active sites and support-tunable electronic structure, and exhibit enhanced activity and high selectivity for the CO2 RR. In this review, we present the recent progress of quantum-theoretical studies on electro- and photo-chemical conversion of CO2 with SACs and frameworks. Various calculated products of CO2 RR with SACs have been discussed, including CO, acids, alcohols, hydrocarbons and other organics. Meanwhile, the critical challenges and the pathway towards improving the efficiency of the CO2 RR have also been discussed.